The influence of olive leaf extract on the activity of antioxidant enzymes in the Hemolymph of Galleria mellonella (L.) (Lepidoptera: Pyralidae) - Tuğba Söküt Açar; Seranay Türkdoğan; Serhat Kaya (Journal of New Results in Science)
The present study has aimed to examine the effects of olive leaf extract on the antioxidant enzyme activity of the invertebrate model organism Galleria mellonella L. (Lepidoptera: Pyralidae) hemolymph. For this purpose, after the olive leaves collected from Çanakkale province were dried at room temperature, the ethanolic extract was obtained with a soxhlet. After the ethanol was removed from the obtained extract in the rotary evaporator, the obtained dry matter was prepared in the phosphate buffer salt, 72 mg mL-1 as the highest dose and the lowest 0.010 mg mL-1 and injected into the larvae reared for the experiment. Hemolymph was collected at 4, 8, 12, 16, and 24-hours post-injection. Catalase (CAT) and superoxide dismutase (SOD) enzyme activities and malondialdehyde (MDA) formation levels were determined spectrophotometrically in the collected hemolymph. According to the results obtained, olive leaf extract decreased CAT and SOD activity in G. mellonella hemolymph at certain doses and increased the amount of MDA. For all enzymes, group, dose, and group-dose interactions were statistically significant. In addition, as a result of the examination made in terms of time, it was seen that the measurement of enzyme activities at the 24th hour was significant. The results of our study show that the antioxidant capacity of the olive leaf cannot be transferred to other living things and even reduces the antioxidant capacity of other organisms.